Atypical teratoid rhabdoid tumor involving the nasal cavities and anterior skull base. Issue 3 (16th November 2015) - Barresi, Valeria; Branca, Giovanni; Raso, Alessandro; Mascelli, Samantha; Caffo, Maria; Tuccari, Giovanni
Abstract : Rhabdoid tumors are a spectrum of neoplasias composed of cells which show rhabdoid morphology but are devoid of skeletal muscle differentiation. These tumors are characterized by inactivation of the INI1/SMARCB1 gene and they have been described in virtually every anatomical site, including the central nervous system (CNS) and sinonasal tract. Rhabdoid tumor of the CNS was named atypical teratoid rhabdoid tumor (ATRT) and it mainly affects children under the age of 3 years with supra‐ or infra‐tentorial location.Herein we report the first case of ATRT infiltrating the nasal cavities and skull base in an adolescent. Due to its unusual location, differential diagnosis was challenging and included several other entities such as sinonasal carcinoma or meningioma. Awareness that ATRT may infiltrate the nasal tract and knowledge of its clinico‐pathological, immunohistochemical and biomolecular features are essential for its distinction from other rhabdoid tumors which more frequently involve this anatomical site and for appropriate therapeutic management.